Bariatric Metabolic Surgery Reduced Liver Enzyme Levels in Patients with Non-Alcohol Fatty Liver Disease - Kirkpatrick, Kennedy; Bobbie Paull-Forney; Hayrettin Okut; Tiffany Schwasinger-Schmidt (Kansas Journal of Medicine, 2021)
Introduction. Approximately 93.3 million Americans are obese (BMI>30) and 51% have non-alcoholic fatty liver disease (NAFLD). Progression of NAFLD can lead to Non-Alcoholic Steatohepatitis (NASH), the leading cause of liver transplant in the United States. This study analyzed liver enzymes following bariatric surgery in NAFLD patients up to one-year post-surgical intervention. Methods. A retrospective analysis of adults with NAFLD who underwent bariatric surgery from 2009 to 2016 was conducted. The primary outcome were transaminase levels following weight loss. Secondary outcomes included effects on blood glucose, lipids, and blood pressure. Results. A total of 130 participants consisting of 80% Caucasian females with an average BMI of 47.5 participated in the study. Reductions were noted in ALT (66.2 to 28.6 units/L) and AST (46.3 to 24.2 units/L) at 1 year post-surgical intervention. Significant reductions were also noted in blood glucose (22.34%; p < .0001), HbA1c (17.11% p < .0001), LDL (19.75% p = .0046), total cholesterol (10.12% p = .0153), and triglycerides (37.21% p < .0001) with an increase in HDL (17.22% p = .0007). Significant correlations between alkaline phosphatase and ALT were noted at six months (p=.0101) and one year (p= .0547) and AST at six months (p=.0009). When separated by obesity class, participants with class II obesity experienced improved outcomes. Conclusions. Data obtained from this study indicated that bariatric surgery reduces liver enzyme levels in NAFLD. These findings suggest that bariatric surgery is a viable treatment option for participants with NAFLD.